Light Pollution Classification and Intervention Based on Assessment Models - Zhu, Xiaotian; Chen, Shudan (Transactions on Environment, Energy and Earth Sciences, 2024)
With the rapid development of science and technology, landscape and outdoor commercial lighting have become essential but also aggravate light pollution, a new form of environmental pollution. This paper develops a light pollution risk level model and an intervention model. Three regions are selected using the TOPSIS model, considering population, precipitation, GDP, artificial light intensity, and sky brightness. An AHP-based intervention model evaluates cost, accident rate, biological comfort, and persistence. Strategies include reducing light duration and controlling nighttime lighting. For cities like Shanghai, using more glass curtain walls can help, while for sunny cities like Kunming, controlling nighttime lighting is effective. Based on previous studies, this paper compares major cities, obtains customised solutions for different cities, and quantifies light pollution risk level indicators.